Mathematical modeling of the effect of stent construction during endoluminal IRE for recanalization of an occluded metal stent - Matkulcik, Peter; Hemzal, Martin; Rohan, Tomas; Cervinka, Dalibor; Novotna, Veronika; Goldberg, Shraga Nahum; Andrasina, Tomas (International journal of hyperthermia, 2025)
BACKGROUND: Intraluminal irreversible electroporation (IRE) can be used for recanalizing occluded metal stents. However, optimal IRE parameters for consistent effects across different stent designs remain unclear. The aim of this study was to simulate the process of stent recanalization in silico by employing finite element analysis. METHODS: A virtual model of an occluded biliary stent with an experimental 3-electrode IRE catheter was developed. Electric field distribution, temperature changes, and potential ablation volumes were simulated across various parameters: IRE voltage (300 - 1300 V), stent wire width (0.1 - 0.5 mm) and stent mesh size (0.7 - 5.58 mm). Simulations incorporated five representative stent types commonly used in clinical practice. 685 unique simulations were conducted, analyzing 1162 unique values. RESULTS: Higher voltages generally led to larger ablation zones and increased temperatures. Thinner stent wires and larger mesh sizes also increased the extent of ablation zone. While in-stent ablation was largely independent of stent design, out-of-stent ablation was significantly impacted by mesh size and tissue thickness between the stent and irreversible electroporation electrodes. Voltages above 1000 V produced significant thermal effects, with substantial volumes of tissue heated above 50 °C. Specific stent designs exhibited variations in maximum temperature (72.1 - 83.1 °C) and ablation volume (8.7 - 14.7 mm3). CONCLUSION: Tailored IRE protocols for different stent designs are required due to differences in in- and out-stent ablation volumes. High voltages (>1000 V) induce both thermal and nonthermal ablation mechanisms.
Keywords: elektroporace; temperature distribution; metal stents; stenty; Humans; lidé; ablation; Models, Theoretical; Electroporation; teoretické modely; computer simulation; Irreversible electroporation; Stents